Peer-victimisation and self-worth in children with and without Developmental Coordination Disorder - Barrett, Nicholas; Piek, Jan; Allen, Linsey; Jones, A.; Louise, M. (The Australian Psychological Society Ltd, 2003)
The relationship between peer-victimisation and self-worth was investigated in a group of children with Developmental Coordination Disorder (DCD: DSM-IV) and control children. Forty-three children aged 7 to 11 years were identified as having mild to moderate DCD as indexed by the McCanon Assessment of Neurological Development (McCarron, 1997),and were matched with 43 control children on age and gender.Peer-victimisation and self-worth were found to be negatively correlated.Although the two groups did not differ significantly on reported self-worth or peer-victimisation, the relationship between these two variables was moderated by group membership. Peer-victimisation accounted for a greater and statistically significant proportion of the variance in girls with mild to moderate DCD. Furthermore,the relationship between peer-victimisation and self-worth in girls with DCD was found to be direct,and not mediated by their perceived competencies.